2017
DOI: 10.2967/jnumed.117.192625
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 68Ga-Prostate-Specific Membrane Antigen PET/CT on Prostate Cancer Management

Abstract: The objective of this study was to assess the impact of Ga-prostate-specific membrane antigen (Ga-PSMA) PET/CT on the management of prostate cancer in patients with biochemical recurrence (BCR). Documented management plans before and afterGa-PSMA PET/CT in 100 patients with BCR were retrospectively reviewed, and changes in plans were recorded. Management changed afterGa-PSMA PET/CT in 39 patients (39%). The management changes occurred in 23 (33.8%) of 68 patients with radical prostatectomy and 16 (50%) of 32 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 14 publications
4
37
0
2
Order By: Relevance
“…Of the remaining 3 articles, one study showed an opposite trend and the other two a reduction or a raise of the DR irrespective of the value of the PSAdt. The possible correlation between the DR of PSMA‐PET and PSAvel was evaluated in seven studies . A positive correlation among DR of PSMA‐PET and PSAvel was found in four of seven studies (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the remaining 3 articles, one study showed an opposite trend and the other two a reduction or a raise of the DR irrespective of the value of the PSAdt. The possible correlation between the DR of PSMA‐PET and PSAvel was evaluated in seven studies . A positive correlation among DR of PSMA‐PET and PSAvel was found in four of seven studies (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The possible correlation between the DR of PSMA‐PET and PSAvel was evaluated in seven studies . A positive correlation among DR of PSMA‐PET and PSAvel was found in four of seven studies (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, positron emission tomography-computed tomography (PET-CT), with tracers such as 18 F-choline, has increasingly played a role in the management of these patients [5,6]. However, sensitivity is only moderate for This article is part of the Topical Collection on Oncology -Genitourinary * Meghana Kulkarni Mkulkarni1@gmail.com detecting nodal metastases [5] or in those with low PSA levels at biochemical recurrence (BCR) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Evaluations have demonstrated a favourable biodistribution and affinity for targeting PSMA [14][15][16]. Whilst 68 Ga-HBED-CC-PSMA PET-CT has been shown to impact management in between 39 and 62% of patients with BCR of prostate cancer after previous definitive treatment and in 21% of patients undergoing primary staging, no such data has yet been reported for 68 Ga-THP-PSMA [17,18].…”
Section: Introductionmentioning
confidence: 99%